On endocytoscopy and posttherapy pathologic staging in esophageal cancers, and on evidence‐based methodology. (29th September 2014) - Chao, Yin‐Kai; Kawada, Kenro; Kumagai, Youichi; Takubo, Kaiyo; Wang, Helen H.
Abstract : The following, from the 12th OESO World Conference: Cancers of the Esophagus, includes commentaries on the value of endocytoscopy to replace biopsy histology for squamous cell carcinoma and the clinical significance of posttherapy pathologic stage in patients with esophageal adenocarcinoma following preoperative chemoradiation; a short discussion of evidence‐based methodology is also included.